Evolution and Drivers of Energy Embodied in Intermediate and Final Trade Between China and the World - Quanzhi Xia; Mengyao Han; Xiaofang Wu (Earth's Future, 2022)
Abstract The increasing fragmentation of global supply chains has led to a new phase of international trade with intermediate products comprising a remarkable share. For China as the biggest energy consumer and trading nation, its energy use related to the trade of intermediate products has not yet been fully understood. To fill the gap, this study develops the concept of embodied energy resources to establish an all‐inclusive energy trade budget for China, from exploitation to intermediate production and to final consumption. By combining the input‐output analysis and structural decomposition analysis, the evolution and drivers of energy resources embodied in China's intermediate and final trade are systematically explored for the period 1995–2018. We find that energy resources embodied in China's intermediate trade grew faster than those in final trade. Mining stood out in intermediate trade, while Transport and Service were prominent in final trade. The Global North played a key role in China's trade for final consumption, whereas the Global South had a close relationship with China in production‐driven intermediate trade. Energy efficiency gains made more obvious contributions to saving energy resources embodied in intermediate trade, while production structure changes posed more evident impacts on energy resources embodied in final trade. Taking full account of trade heterogeneity, this study highlights the importance to distinguish intermediate trade from final trade, especially when the former accounted for around 80% of energy use embodied in China's international trade.